2019
DOI: 10.3390/jcm9010038
|View full text |Cite
|
Sign up to set email alerts
|

Presence of ROS in Inflammatory Environment of Peri-Implantitis Tissue: In Vitro and In Vivo Human Evidence

Abstract: Analyses of composition, distribution of cellular and extracellular matrix components, and molecular analysis of mitochondria related genes of bone loss in the presence of inflammatory environment in humans was the aim of the present project. As a human model we chose peri-implantitis. Morphological analyses were performed by means classical histological, immunohistochemical, and SEM (scanning electron miscroscopy) test. Gene expression analysis was performed to evaluate epithelium maturation, collagen fiber p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 31 publications
(33 reference statements)
2
29
0
Order By: Relevance
“…It should also be noted that excessive collagenization was detected in the connective tissue in all cases of peri-implantitis as demonstrated by transmission electron microscope. Our results are in agreement with Mijiritsky et al (14) who demonstrated bundles of collagen fibers in the connective tissue underneath the epithelium in cases of periimplantitis. This finding could be mediated by cytokine pathway that is initiated by particles of implant material and then resulted in collagen production (26) .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…It should also be noted that excessive collagenization was detected in the connective tissue in all cases of peri-implantitis as demonstrated by transmission electron microscope. Our results are in agreement with Mijiritsky et al (14) who demonstrated bundles of collagen fibers in the connective tissue underneath the epithelium in cases of periimplantitis. This finding could be mediated by cytokine pathway that is initiated by particles of implant material and then resulted in collagen production (26) .…”
Section: Discussionsupporting
confidence: 94%
“…Our present results are consistent with those of Mijiritsky et al (14) who reported an inflammatory infiltrate underneath the epithelium with collagen fibers in peri-implantitis tissue as well as a differ- ent distribution of blood vessels throughout the connective tissue. In contrast to our findings, some other studies have demonstrated an inflammatory infiltrate that was of T-cell dominated one in both normal gingival and peri-implantitis tissues (15,16) .…”
Section: Discussionsupporting
confidence: 93%
“…Excessive ROS cause apoptosis and activation of inflammatory signaling cascades, leading to incomplete recovery of damaged tissue [ 1 , 2 ]. For example, the high level of ROS surrounding dental implants results in uncontrolled inflammation with bone loss, and elevation of ROS during autologous or allogenic hematopoietic stem cell transplantation (HSCT) can result in serious toxic problems [3][4][5] . It has been reported that pro-oxidant methemoglobin (Fe 3 + ) released from lysed blood cells and H 2 O 2 derived from the lysis of epithelial or immune cells during surgical incision of implantation process are associated with ROS-mediated failure of tissue engineering approaches [ 6 , 7 ].…”
mentioning
confidence: 99%
“…Wear particles can be generated from the surface of the implant, but also from the contact point of modular implants [62]. The range and size of particles wear debris are heterogeneous: smaller particles are generated during repeated rolling movements and by sliding and rotational motion on bearing surface by adhesion and abrasion, while larger particles originate from surface fatigue [63]. The size of wear particles isolated from periprosthetic tissue has a range of 0.1 to 1000 µm, but the majority belongs to the range of 0.1 to 10 µm.…”
Section: Oxidative Stress In Aseptic Periprosthetic Osteolysismentioning
confidence: 99%